2022
DOI: 10.1088/2631-6331/ac586c
|View full text |Cite
|
Sign up to set email alerts
|

Abrasive water jet machining of coir fiber reinforced epoxy composites: a review

Abstract: Natural fiber-reinforced composites are progressively being earning attention in the aerospace, automotive, aeronautics, and marine sectors due to their good strength-to-weight ratio, long-lasting, and cost-effective. Traditional machining methods have trouble machining such composite materials. However, Abrasive Water Jet Machining (AWJM) provides an alternative quality machining method that can be accomplished by regulating various process variables. The efficiency of the AWJM method is the subject of extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…Figure 11 shows the static modulus of elasticity of the control mix and concrete containing marble dust and foundry sand subjected to increased temperatures of 200 °C, 400 °C, 600 °C, 800 °C, and 1000 °C. The static modulus of elasticity was measured to see how the deformation capacity of the concrete mixtures changed over time [ 17 , 28 , 35 , 39 , 94 , 95 , 96 , 97 , 98 ]. In all cases of concrete exposed to high temperatures, the static modulus of elasticity was shown to be reduced.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 11 shows the static modulus of elasticity of the control mix and concrete containing marble dust and foundry sand subjected to increased temperatures of 200 °C, 400 °C, 600 °C, 800 °C, and 1000 °C. The static modulus of elasticity was measured to see how the deformation capacity of the concrete mixtures changed over time [ 17 , 28 , 35 , 39 , 94 , 95 , 96 , 97 , 98 ]. In all cases of concrete exposed to high temperatures, the static modulus of elasticity was shown to be reduced.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 12 shows the dynamic modulus of elasticity of the control mix and concrete containing marble dust and foundry sand subjected to increased temperatures of 200 °C, 400 °C, 600 °C, 800 °C, and 1000 °C. Elevated temperature causes considerable damage to the cement matrix, according to the dynamic modulus of elasticity [ 17 , 28 , 35 , 39 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ]. In all cases of concrete exposed to extreme temperatures ranging from 200 °C to 1000 °C, the dynamic modulus of elasticity was shown to be reduced.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the permeability result, it is also found that coefficient of permeability with 2 percent soap solution is very much less in comparison with 0 percent soap solution. From the observation of SEM images, it can be said that soap solution helps in filling the voids of concrete which ultimately helps in reduction in permeability [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. EDX analyses of concrete with 0% (M1) and 2 % (M6) soap solution are shown in Figure 9 and Figure 10 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, exceeding the plasticizer content beyond 20% in the composition may lead to the separation of phases in a part or whole of the body. The opportunity of PLA in packaging materials expands further due to the incorporation of nanoparticles [259] since nanoparticles bring exceptional rheological changes in the structure of PLA, resulting in low density, stiffness, thermal and mechanical stability, and recyclable packaging material.…”
Section: Industrial Scope Of Plamentioning
confidence: 99%